Online learning during a global pandemic: Perceived benefits and issues in higher education - Weldon, Anthony; Ma, Will W K; Ho, Indy M K; Li, Emil; | | (Knowledge management & e-learning, 2021)
The COVID-19 pandemic has created substantial challenges across higher education, requiring academic institutes to conduct all teaching, learning, and assessments remotely online. To obtain a stronger understanding of the opinions of teachers and students in Hong Kong during this period, an anonymous online survey was distributed to all teachers and students at a higher education institute. Overall, 48 teachers and 425 students responded to the survey. This paper specifically analyzes the responses to open-ended questions from the survey to identify key topics and concepts. Open coding was used to obtain key terms, which were further grouped into categories. Results indicated that higher education teachers and students had similar issues (e.g., access to digital devices and software) and benefits (e.g., flexible scheduling and time arrangements) regarding online education. However, some categories were reported as both issues and benefits by teachers and students (e.g., communication/interaction), demonstrating that individual circumstances, abilities, preferences, and experiences, may influence satisfaction levels. Furthermore, results indicated that the delivery of quality online education enforced during a pandemic requires a multi-factorial and tailored approach. The information presented in this study will help higher education institutes to develop, redefine, and re-conceptualize online learning initiatives.